Competitiveness analysis of ESG qualified investment funds available in Hungary - Vancsura, László; Bareith, Tibor (Public Finance Quarterly, 2025)
The aim of this study is to examine the factors influencing the annual returns and total expense ratio (TER) of equity funds operating in Hungary, with a particular focus on funds with ESG ratings. The study is based on data from the period between 2021 and 2023 and targets public equity investment funds. We used OLS and quantile regression methods for the analysis, taking into account the extreme inflationary environment and the economic changes caused by COVID-19 and the Russian-Ukrainian war. The results show that ESG ratings have a significant negative impact on annual returns according to the OLS model, while based on quantile regression, this negative impact is particularly evident in the upper quantiles of returns. In contrast, the impact on the total expense ratio is not significant, although funds focusing on emerging markets show significantly higher cost levels in the higher quantiles. In addition, it can be concluded that funds with higher net asset values operate at lower costs, which indicates the prevalence of economies of scale. The age of the funds shows a positive correlation with the total expense ratio, indicating that older funds typically have higher operating costs. Our results contribute to a better understanding of the performance and cost structure of ESG funds and highlight that sustainability considerations should be assessed in a differentiated manner in terms of both returns and costs when making investment decisions.